Afghanistan in SAARC: A Critical Assessment of Organisational Expansion. (September 2015) - Ahmed, Zahid Shahab; Zahoor, Musharaf
Ever since the formation of the South Asian Association for Regional Cooperation (SAARC) in 1985, the motivation for the expansion of the Association has been expressed by its founding members. The prospective expansion comes naturally to international organisations (IOs), visible in the increase in membership of the European Union (EU) from six to 28 European countries. Similarly, the Association of Southeast Asian Nations (ASEAN) has doubled its membership since its inception. SAARC membership grew in 2007, with the inclusion of Afghanistan. Yet, there is limited assessment on the opportunities and challenges that have arisen since Afghanistan's arrival in SAARC 10 years ago. This article provides an evaluation of Afghanistan within SAARC, and a further comparison to processes of enlargement in the EU and ASEAN. It is argued that Afghanistan's membership poses significant challenges for SAARC, owing to its political instability. Its stature as a war-torn country has meant that it has failed to prioritise its role in the Association. Furthermore, the membership of Afghanistan has significantly contributed to the conflict relationship between Afghanistan and Pakistan, further constraining SAARC processes and agendas.